Synthetic Fillers in Facial Cosmetic Surgery-Different Categories Discussion of Rheologic Properties - Nima Dehghani; Mohadeseh Azarsina; Xaniar Mahmoudi (Journal of Craniomaxillofacial Research)
Introduction: The pursuit of facial rejuvenation and aesthetic enhancement has evolved significantly over time. Early techniques, such as fat transplantation in the 1890s, paved the way for modern dermal fillers (DF), which have become a cornerstone of minimally invasive cosmetic procedures. Today, filler injections are among the most popular treatments for soft tissue augmentation, facial volumization, and body contouring. This review explores the development of dermal fillers, their current applications, and the key physical properties that differentiate them. Materials and Methods: A comprehensive literature review was performed using scientific databases (PubMed, Scopus) to identify peer-reviewed articles, clinical studies, and manufacturer data on dermal fillers. The analysis focused on: - Historical evolution of filler materials. - Chemical compositions and physical properties. - FDA-approved clinical applications. - Reported efficacy and safety profiles. Results: Dermal fillers have undergone significant advancements, offering improved safety, durability, and natural results. Their versatility allows for tailored treatments in facial rejuvenation and beyond, making them indispensable in aesthetic medicine. Conclusion: As DF technology continues to evolve, understanding their properties ensures optimal patient outcomes. Their integration into cosmetic practice underscores their importance in meeting the growing demand for non-surgical aesthetic solutions. Keywords: Dermal fillers; Synthetic fillers; Hyaluronic acid; Temporary dermal fillers.